Finding Spirits in Spirituality What are We Measuring in Spirituality and Health Research? - Laird, Lance D.; Curtis, Cara E.; Morgan, Jonathan R. (2017)
What are we asking when we ask about spirituality? When research subjects check survey boxes for “religiosity” and “spirituality” measures on health surveys, those of us who use them often assume that these responses indicate a relationship with—or reaction against—normative, conventional, Protestant-shaped religious practice and experience. We present a qualitative interview study of 13 low-income mothers with a history of depression, analyzing their descriptions of spiritual and religious coping practices. On the basis of a focused analysis of four mother’s narratives, we argue that conventional survey answers may frequently hide more than they reveal about people’s cultural, religious, and idiosyncratic experiences with ghosts, spirits, magic, and haunting presences that are relevant, sometimes integral, to illness and healing. We demonstrate that listening to participants’ narratives challenges researchers’ unconsciously normative assumptions and ought to help us reshape our understanding of the ways spirituality and religion influence health in a hyperdiverse society.
Keywords: Spirituality; Religion; Depression; Communication with the dead; Culture and measurement bias; Ghosts; Magic; Measurement; Methodology; narrative analysis; Poverty -- stress -- and depression; Spirits; Spiritual coping; Trauma